Dinâmicas territoriais e interações espaciais: o circuito espacial produtivo da avicultura de corte no município de Pocinhos-PB - Buriti, Maria Marta dos Santos (2016)
Given the technical, political, economic and social which began to rationalize the geographical space in the globalization period, the feature of the territory is indicative of the progress of the capitalist mode of production in the different directions of space and the various local scenes. At the moment of our history, the geographical dissociation of production as a strategy for better flow of production processes clarified the concepts of productive spatial circuit and cooperation circles as fundamental theoretical and analytical tools for understanding the movement of economic activities in space and its developments in the organization, regulation and uses of the territory. In accordance with this thinking, this study points to a reading of the territorial dynamics of productive spatial circuit of poultry making in the municipality of Pocinhos-PB, from the action of two forces that, at different times, were made hegemonic. These forces, Azeven company and Agrobusiness Cialne in the light of competitive, organizational and individual technical factors were responsible for creating spatial interactions and distinct territorial dynamics in the productive space circuit of poultry making, which reverberated directly in the territory uses. Given this context, the objective of the research is to understand the spatial interactions and territorial dynamics in the productive space circuit court of poultry and its consequences in the territory of uses in Pocinhos-PB. The study revealed that, under the hegemony of Azeven action in the productive spatial circuit, the spatial interactions and territorial dynamics were designed from relational plots on a small scale, which reflected the accommodation of the competing demands on a forced circulation space inside the state of Paraiba. Already, under the hegemony of Cialne action in the productive spatial circuit of poultry making, the expansion of productive contexts and the expansion of flow spaces corroborated for the establishment of spatial interactions and more complex territorial dynamics that reached the complementarity levels necessary for the operation of the production circuit on a regional scale. Keywords: Spatial Productive Circuit, Poultry Production, Territory, Spatial Interactions.